Oscillation theorems for nonlinear differential equations - Jelena Manojlović (Electronic Journal of Qualitative Theory of Differential Equations, 2000)
We establish new oscillation theorems for the nonlinear differential equation $$[a(t)\psi(x(t))|x'(t)|^{\alpha-1}x'(t)]'+q(t)f(x(t))=0, \alpha>0$$ where $a,q:[t0,\infty)\rightarrow R, \psi,f:R\rightarrow R$ are continuous, $a(t)>0$ and $\psi(x)>0$, $xf(x)>0$ for $x\not=0$. These criteria involve the use of averaging functions.